UPAYA PENINGKATAN PENGETAHUAN TENTANG PENGGUNAAN OBAT YANG BENAR MELALUI EDUKASI DAGUSIBU OBAT PADA KADER POSYANDU - Mildawati, Ratna; Prasetyo Nugroho , Bandhi; Hamida Oktavia , Laura (Jurnal LENTERA, 2025)
Each medication has beneficial effects on the body but also carries harmful side effects. Currently, Indonesian society is becoming increasingly accustomed to the use of various types of medications for purposes such as treating illnesses, managing conditions, or as supplements to support daily activities. Therefore, knowledge about medications is essential for the community to ensure their proper and effective use. The DAGUSIBU program was initiated to enhance public understanding of the wise use and management of medications. Its goal is to increase public awareness and comprehension of proper and accurate medication management and monitoring. The methods employed include lectures using educational leaflets and PowerPoint presentations, discussions, and Q&A sessions. The educational outcomes show a significant improvement: prior to the educational intervention, only 27.3% of respondents had good knowledge. Following the intervention, this figure increased to 90%, representing a 60% improvement. This demonstrates that the activity successfully enhanced public understanding of rational medication use. Posyandu cadres can actively contribute to delivering DAGUSIBU-related education to the community.